WRITING DESCRIPTIVE TEKS BASED ON “PROMBLEMS BASED INSTRUCTION (PBI) AT X STUDENTS IN SMK TRIATMA JAYA DALUNG - Putu Ayuning January Punia Putri (RETORIKA: Jurnal Ilmu Bahasa, 2018)
ABSTRACT This study aims to describe the use of instruction-based instructional model, knowing what kind of error students find in writing descriptive text as well as to to improve students' self confidence in English, especially in descriptive writing writing skill. The sample of this research is class X students of SMK Triatma Jaya Dalung consisting of 25 students. The study was conducted in January and February 2018 from two research cycles. The first cycle for the pretest and the second cycle for posttes. The results of the study found that the application of Problem Based Instruction (PBI) based learning process can improve the writing of paragraphs of argument on Class X SMK Triatma Jaya Dalung. Application of learning with the PBI model can also increase student learning activities. The mistakes often made by the students of class X of SMK Triatma Jaya Dalung in writing descriptive text paragraphs among them in terms of creativity of topic development, in terms of organization that includes the structure of argumentation and in terms of vocabulary selection, language use, and mechanical aspects, the argumentation has several deficiency. Management of learning with the right PBI model can improve the skills of writing paragraphs of descriptive text of students of Class X SMK Triatma Jaya Dalung. First, the PBI model is more fun in learning to write descriptive text paragraphs. Secondly, the PBI model is more effective in writing descriptive text paragraphs because the problems that exist in reading are easier and inspire students in generating ideas. Third, the PBI model can enhance student creativity. Keywords: writing, descriptive text, problem based instruction